If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1b = a + -3abx Reorder the terms: -1b + 2x = a + -3abx Solving -1b + 2x = a + -3abx Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '3abx' to each side of the equation. -1b + 3abx + 2x = a + -3abx + 3abx Reorder the terms: 3abx + -1b + 2x = a + -3abx + 3abx Combine like terms: -3abx + 3abx = 0 3abx + -1b + 2x = a + 0 3abx + -1b + 2x = a Add '-2x' to each side of the equation. 3abx + -1b + 2x + -2x = a + -2x Combine like terms: 2x + -2x = 0 3abx + -1b + 0 = a + -2x 3abx + -1b = a + -2x Reorder the terms: -1a + 3abx + -1b + 2x = a + -2x + -1a + 2x Reorder the terms: -1a + 3abx + -1b + 2x = a + -1a + -2x + 2x Combine like terms: a + -1a = 0 -1a + 3abx + -1b + 2x = 0 + -2x + 2x -1a + 3abx + -1b + 2x = -2x + 2x Combine like terms: -2x + 2x = 0 -1a + 3abx + -1b + 2x = 0 The solution to this equation could not be determined.
| 2x+-3=4 | | f(x)=x^2+8x+32 | | 1-7y=1 | | r=(90-3x)(12+x) | | 35y+4=24 | | 11.49-5.15= | | 895/9=-10/3(9/2x+5/3) | | 30=9h+12 | | 7k-3=12 | | 10m-20=60 | | 6t-12=12 | | -2/3=r/6 | | 2x+13=-47x-10x | | 24-6x=9-9x | | 5(5y-6)=21y-30 | | 2(m-8)-3m=-8 | | c+2(d-5c)+14d= | | x^2=5x^2+4x+38 | | 5+11x=-5+x | | 32=9g-4 | | 5x-6=10+11 | | 21=3(x-9) | | x*10-98=x*4-14 | | 600+73= | | 6(2(y+x))=0 | | 3x+2=14+2x | | 3.5a-2=-.5a+4 | | .25x*.25x=.8 | | -75h^3+90h^2y-27hy^2= | | 4-4x=999 | | 17x+98y=199009 | | 8x+4=2x+4 |